(untitled) (The Pakistan Development Review, 1986)
Consumer subsidies have been playing an increasing role in Pakistan since Independence. Largely as left-over economic controls of World War II, a number of sophisticated instruments! have been applied with different objectives at different times, surprisingly similar to those applied in Europe. It is interesting to see how South Asian countries, with their common colonial heritage of food administration and agricultural market and price regulations, developed different approaches after Independence, and to analyse the extent to which these can be explained by their different resource endowments and political ambitions and objectives.